The Roll Away Saloon: cowboy tales of the Arizona strip - Rider, Rowland W., 1890-1984, author; Paulsen, Deirdre, author; Utah State University Press, publisher (Colorado State University. Libraries, 1985)
With his animated tales of Zane Grey, Butch Cassidy, and the Robbers Roost gang, Rider creates an engaging and believable picture of the joys and hardships of cowboy life.--Provided by publisher.
Part 1. At Home on the Range. The Roll Away Saloon -- S'n' Ostrich -- Ground Owls -- Betting Gold Pieces -- Shoeing Little Dickie -- Pal -- Indian Trading -- Fighting Stallions -- Old Mose Indian -- Indian Medicine -- Butch Cassidy's Escape -- Of Cowboys and Weather -- Ten Requirements to Become a "Top-Notch Cowboy" -- Cattle Brands on the Arizona Strip and in Kane County -- Songs of the Range -- Part 2. Of Guns, Gold and Near Starvation. Seven Bags of Gold -- Buying Out Emett (Or, Looking Down the Barrel of a Six-Shooter) -- Enter Zane Grey -- The Black Stallion -- Julius F. Stone Expedition -- Part 3. Three Capers on the Kaibab. Scaring President Roosevelt -- The Death of Yellow Hammie -- Roping Wild Steer -- Riding the Points -- The Lone Timber Wolf -- Buffalo Jones "Outbuffalos" a Buffalo -- "Darting" From a Buffalo -- Branding Buffalo -- Old Cattalo -- Lightning in the Forest -- Prospecting Without a Mule: Or, Tragedy in the Grand Canyon.
Rowland W. Rider as told to Deirdre Paulsen.
Keywords: Frontier and pioneer life -- Utah -- Kanab; Frontier and pioneer life -- Arizona -- Grand Canyon; Frontier and pioneer life -- Arizona -- Arizona Strip; Cowboys -- Utah -- Kanab -- Biography; Cowboys -- Arizona -- Grand Canyon -- Biography; Cowboys -- Arizona -- Arizona Strip -- Biography; Folklore -- Utah -- Kanab; Folklore -- Arizona -- Grand Canyon; Folklore -- Arizona -- Arizona Strip; Kanab (Utah) -- Social life and customs; Grand Canyon (Ariz.) -- Social life and customs; Rider, Rowland W., 1890-1984